Decoding Protein Gas‐Phase Stability with Alanine Scanning and Collision‐Induced Unfolding Ion Mobility Mass Spectrometry. Issue 1 (28th December 2020) - Bellamy‐Carter, Jeddidiah; O'Grady, Louisa; Passmore, Munro; Jenner, Matthew; Oldham, Neil J.
Abstract: Native mass spectrometry is a widely used tool in structural biology, providing information on protein structure and interactions through preservation of complexes in the gas phase. Herein, the importance of intramolecular non‐covalent interactions in the gas phase has been studied by alanine scanning and collision‐induced unfolding (CIU) ion mobility‐mass spectrometry. Mutation of specific polar and ionic residues on the surface of an acyl carrier protein (ACP) were found to destabilise the compact gas‐phase structure with mutants E31A, D32A, D41A and D65A being particularly destabilised. Molecular dynamics simulations of the ACP 7+ and 8+ ions showed extended intramolecular interactions, resulting from sidechain collapse of polar surface residues, which were confined to the gas phase and consistent with the CIU data. These findings provide evidence for the importance of specific ionic residues, and their interactions, in the maintenance of compact protein gas‐phase structure. Abstract : Non‐covalent intramolecular interactions of gas‐phase proteins can be discovered from differential stability of alanine mutants. Removal of polar and ionic surface residues from proteins, by alanine scanning, destabilises gas‐phase protein structures as measured by collision induced unfolding. Molecular dynamics helps to decode interactions disrupted by this removal.